Edward Everett Hale the writings of an economic maverick. - Samuels, Warren J.; Biddle, Jeff E. (Emerald, 2001)
Edward Everett Hale was a leading member of the institutionalist group at the University of Texas. More radical than his better known colleague, Clarence E. Ayres, Hale influenced many students - originally through his lectures rather than his publications, which were few in number. This collection assembles materials on Hale, unpublished writings by him, and sets of lecture notes from his courses.
Keywords: Business & Economics -- Economic History.; Social Science -- General.; Economic theory & philosophy.; Economics.; elektronické knihy; electronic books